A qualitative study on self-monitoring of blood glucose by patients with type 2 diabetes mellitus using insulin in a Malaysian hospital / Ong Woon May - Ong, Woon May (2014)
Self-monitoring of blood glucose (SMBG) improves glycaemic control and enhances patient empowerment. It is particularly useful for diabetes mellitus (DM) patients who are using insulin as it facilitates insulin titration and detection of hypoglycaemia as well as hyperglycaemia. Despite this, SMBG remains underutilised in many countries, including in Malaysia, as only 15.3% of the patients with type 2 diabetes mellitus (T2DM) practised SMBG. This study was conducted to explore the views and experiences on SMBG by patients with T2DM using insulin. Factors influencing SMBG practice as well as their suggestions to improve such practice were also explored. Qualitative methodology was employed in this study. Semi-structured, individual indepth interviews were conducted on patients with T2DM using insulin who have practised SMBG. Patients were selected from the primary care family clinic of the University Malaya Medical Centre in Malaysia. Patients were purposively sampled from different age groups, ethnicity, educational levels and levels of glycaemic control [as reflected by the glycosylated haemoglobin (HbA1c) levels] to achieve patient variation in sampling. All interviews were conducted using an interview topic guide and were audio-recorded, transcribed verbatim, checked by an independent person, and analysed using a thematic approach. A total of 15 patients were interviewed and thematic saturation was reached. The themes that emerged under the patients’ views and experiences on SMBG included: initiation of SMBG; feasibility and practice patterns of SMBG; actions in response to blood glucose readings; and the emotions related to SMBG. Factors that influenced SMBG practice were mainly related to equipment, psychological and social aspects. Barriers for practising SMBG included: cost of test strips and needles; unavailability of test strips and needles; lack of reliability; inconvenience; frustration related to high blood glucose readings; perception that iv SMBG was only for insulin titration; fear of needles and pain; lack of motivation, knowledge and self-efficacy; forgetfulness; lack of patient education; stigma; and unconducive workplace. Facilitators for practising SMBG were: desire to know if the blood glucose levels were controlled; desire to please the physician; and motivation from family. Suggestions by the participants to improve SMBG practice included: cost reduction; patient attitudinal and behavioural change; and explicit patient education by healthcare providers. The findings in this study revealed that healthcare providers can affect patients’ SMBG practice and that abnormal blood glucose readings can change their behaviour, where negative emotions may lead to their poor adherence to SMBG. Healthcare providers should be made aware of the impact of their consultation in order to improve patients’ utilisation of SMBG and decrease the negative impact of ‘poor’ blood glucose readings on their SMBG practice. Policy makers should consider the impact of barriers to SMBG such as cost and accessibility issues to encourage optimal utilisation of SMBG.